CAU-BAU-KAN : A STORY OF THE CONTRIBUTION OF TIONGHOA TO THE NATION-BUILDING OF INDONESIA - Yohanes Hartadi (Soegijapranata Catholic University, 2002)
Ethnic and racial riots still happen in Indonesia. There must be a deeply-rooted reason for that. Remy Sylado's Cau-Bau-Kan concerns with a racial enmity between the pribumi and the Tionghoa (Indonesian Chinese). The enmity is growing from the old times when the Dutch and the Japanese colonizrd the country. They spreaded falses ideas against the Tionghoa among the pribumi. The Dutch also had the TIonghoa live in a particular area so that they were isolated from the interraction with the pribumi. Most pribumi do not understand these causes, they even produce stereotypes for generations. Cau-Bau-Kan tries to counter the stereotypes saying that the Tionghoa did not contribute anything for the nation-building of Indonesia